Cold War ruins: Transpacific critique of American justice and Japanese war crimes - Yoneyama, Lisa (Duke University Press, 2016)
Introduction : transpacific cold war formations and the question of (un)redressability -- Liminal justice : Okinawa -- Liberation under siege : Japanese women -- Sovereignty, apology, forgiveness : revisionisms -- Contagious justice : Asian/America -- Complicit amnesia : for transformative knowledge